The Exceptional Qur’ān: Flexible and Exceptive Rhetoric in Islam's Holy Book: (by Johanne Louise Christiansen) (American Journal of Islam and Society, 2024)
Johanne Louise Christiansen’s The Exceptional Qur’ān: Flexible and Exceptive Rhetoric in Islam’s Holy Book offers a lucid study of Qur’ānic exceptions and flexibilities. The book begins with a critical discussion of the Muslim creed. In the Introduction, the author argues that “the exceptive particle illā (‘except,’ ‘but,’ or ‘unless’) found in the Shahādah , is neither an exception nor a general or absolute denial” (1). However, she claims this exception is false because it is “self-contradictory” and “paradoxical in nature.” This discussion includes a claim that authoritative scholars of the Muslim tradition, such as al-Qurṭubī (d. 671/1272), did not consider such exceptions to be a comprehensive and absolute exception, but rather to represent a categorical proposition or argument. The book consists of seven chapters and an Introduction. In the Introduction, Christiansen highlights the categorical or absolute aspects of exception in the Qur’ān.